ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MENGGUNAKAN LANGKAH-LANGKAH POLYA PADA PESERTA DIDIK KELAS VIII SMP ADABIAH PADANG - Rahma, Husniatul (Departemen Matematika, 2023)
Problem solving ability is one aspect that is the main focus of learning. Students use the knowledge they already have to solve the given problem. One way to solve the problem is to use Polya's steps, namely understanding the problem, planning a solution, implementing a settlement plan, and checking again. The low ability of students' mathematical problem solving is caused by the habits of students in solving problems according to what is taught by the teacher and the lack of giving mathematical problem solving questions which results in students lacking skills in solving mathematical problem solving ability questions. Based on these problems, the formulation of the research problem is how the mathematical problem solving abilities of SMP Adabiah Padang students in the material of Triangles and Quadrilaterals are viewed from Polya's steps. This study aims to describe and analyze students' mathematical problem-solving skills using Polya's steps on triangles and quadrilaterals in class VIII SMP Adabiah. This type of research is descriptive in nature, because the research subjects were selected using the target sampling method. Tests and interviews were used as data collection methods, while the analytical methods used in this study were descriptive analysis and data triangulation. As a result, the average score of mathematical problem solving abilities at the problem understanding stage is 0,48, the average score at the calculation planning stage is 0,45, and the average score at the calculation plan implementation stage is 0,37. And 0.18 at the verification step. Therefore, the lowest average score is reviewed in the last step, and the highest average score is taken as the problem understanding step.Keywords– Problem-Solving, Polya's steps, Triangle and rectangular